Technological Change, Technological Catch-up, and Capital Deepening: Relative Contributions to Growth and Convergence - Kumar, Subodh; Russell, R. Robert (American Economic Review, 2002)
We decompose labor-productivity growth into components attributable to (1) technological change (shifts in the world production frontier), (2) technological catch-up (movements toward or away from the frontier), and (3) capital accumulation (movement along the frontier). The world production frontier is constructed using deterministic methods requiring no specification of functional form for the technology nor any assumption about market structure or the absence of market imperfections. We analyze the evolution of the cross-country distribution of labor productivity in terms of the tripartite decomposition, finding that technological change is decidedly nonneutral and that both growth and bipolar international divergence are driven primarily by capital deepening.